Reading workshops to encourage STEAM methodologies in Upala, Costa Rica - Carvajal Alfaro , Vanessa (2025)
The extension project "Implementing STEAM Methodologies for Teaching Sustainable Cities through Robotics to Children in Upala Canton" promotes educational robotics as a tool for bridging technological gaps. However, regardless of the subject matter taught or the methodology employed, reading constitutes a fundamental pillar of children's education. Therefore, the objective of this article is to share the experience of conducting reading workshops and a literary event as strategies to stimulate reading among children in Upala Canton. The project was developed with the support of the Socio-Educational Management Unit, responsible for the Canton's Public Library. The library facilitated the dissemination and registration for the workshops. Captive audiences within selected schools in the impact districts, particularly in border areas, were also utilized. The workshops were participatory, employing various techniques to strengthen reading comprehension and fluency competencies, as well as vocabulary acquisition. Work specifically focused on scientific literature concerning environmental protection, wildlife, and the Sustainable Development Goals (SDGs). Ninety-minute workshops were delivered to groups of 25 children. As a result, competencies were strengthened in 798 children through the various activities. One of the most crucial aspects of fostering children's reading development is instilling a need to read. Consequently, if children successfully comprehend texts and derive enjoyment from them, this will reinforce independent reading habits. These habits will enable them to engage with literary experiences throughout their academic and personal development.